Solvent Extraction of Palladium(II) with 2-Ethylhexyl Benzimidazole Sulfide from Hydrochloric Acid Media - Feng, Shaoping; Huang, Zhangjie; Li, Pengwei (Asian Journal of Chemistry, 2011)
The solvent extraction of Pd(II) from hydrochloric acid solutions were investigated using 2- ethylhexyl benzimidazole sulfide (EHBMS) in presence of toluene. Pd(II) was strongly extracted by a lower concentration 2-ethylhexyl benzimidazole sulfide in a lower concentration hydrochloric acid solution. Extraction parameters of Pd(II), including 2-ethylhexyl benzimidazole sulfide concentration, contact time of aqueous and organic phases, organic/aqueous (O/A) phase ratio and H+ concentration of aqueous phase, were studied. The optimal extraction parameters were obtained and summarized, 2-ethylhexyl benzimidazole sulfide concentration 0.005 mol L-1, organic/aqueous (O/A) phase ratio 1.0, H+ concentration of aqueous phase 0.2 mol L-1 and contact time of two phases 15 min. Stripped of Pd(II) from loaded organic phase was performed using thiourea solution (1.0 mol L-1).